Nevus sebáceo cerebriforme: uma rara apresentação - Roberto Rheingantz da Cunha Filho; Aline Peluso Fezer; Nádia Aparecida Lorencette (Sociedade Brasileira de Dermatologia, 2015)
AbstractA 13-year-old boy presented congenital, raised, yellowish colored plaques with fibroelastic consistency, which were velvety in appearance, alopecic, with clearly defined limits and sulci or well-marked meandering invaginations, a cerebriform appearance on the upper part of the right ear, accompanied by alopecia in the temporomandibular region-parietal. The lesion was asymptomatic. Histopathologic examination revealed acanthosis, hyperkeratosis, papillomatosis and follicular plugging in the epidermis. The upper dermis showed underdeveloped hair follicles with sebaceous glands, consistent with sebaceous nevus. There were no skeletal, cardiological, ophthalmological or neuropsychomotor changes; nor were there any records of relevant pathologies in the family history. The patient complained of his appearance, experiencing aesthetic and social issues. Following a diagnosis of cerebriform nevus sebaceous, complete excision was performed with excellent aesthetic results.